Psychoneuroimmunology Approach to Improve Recovery Motivation, Decrease Cortisol and Blood Glucose of DM Type 2 Patients with Dhikr Therapy - Rifka Pahlevi; Suhartono Taat Putra; Sriyono Sriyono (Jurnal Ners, 2017)
Introduction: Blood glucose levels are controlled when the management of diabetes success. Positive perception of the strength of the spiritual aspect will improve the motivation of patients with type 2 diabetes to control it. The purpose of this study was to determine the effect of dhikr based on psychoneuroimmunology (PNI) on blood glucose levels of patients with type 2 diabetes.Methods: This study used quasi-experiment with pre-test and post-test control group design. Samples were taken from the population of patients with type 2 diabetes who were hospitalized in the Internal Medicine Rumkital Dr. Ramelan Surabaya with purposive sampling techniques. Data taken include the general characteristics of respondents, cures motivation, cortisol levels and fasting blood glucose levels. Collecting data using questionnaires and laboratory test, then analyzed using paired t-test and independent t-test, with α value <0.05.Results: Statistical test showed that the motivation to recover increased (p = 0.001), cortisol levels fall (p = 0.058) and a drop in blood glucose levels (p = 0.028) after administration of dhikr therapy in patients with diabetes mellitus type 2. There was a significant difference in increased of recovery motivation between patient conduct zikr therapy and patient cared (p = 0,000).Conclusion: Dhikr therapy increases the motivation of patients with type 2 diabetes by strengthening awareness and spirituality belief in Allah make positive stress perception. Positive stress perception will affect the stress response and improved regulation of blood glucose through the HPA axis to suppress the secretion of CRH, ACTH, and cortisol.